Capacitated Multi-item Lot Sizing Problem with Client Prioritization in Tire Industry. Issue 1 (2021) - Koch, Cyril; Arbaoui, Taha; Ouazene, Yassine; Yalaoui, Farouk; Brunier, Humbert De; Jaunet, Nicolas
Abstract: This paper addresses a dedicated lot-sizing problem from off-the-road tire industry. This case study considers a multi-item capacitated lot sizing problem with assignment on unrelated parallel machines. Several specific constraints imposed by the industrial context are considered such as the limitation of number of mold setups, the number of campaign ending per weeks and the demand class prioritization. A novel mixed integer linear program is introduced to solve this problem taking into account several primary and secondary optimization criteria. In order to analyze the sensitivity of the objective function over the different criteria weights, Taguchi method is carried out based on real data issued from the industrial case.